Tiga Novel Karya Okky Madasari: Perspektif Kriminologi Lingkungan - Ahmad Burhanuddin; Anas Ahmadi; Ririe Rengganis (Universitas Sebelas Maret, 2024)
Human survival depends heavily on environmental sustainability. If the ecosystem is disturbed, the welfare of human life will also be disturbed. Nature is a bridge for writers and writers of literary works to convey the atmosphere, image, setting, or major themes that exist in literary works. Three novels by Okky Madasari are one of the children's novels in which there are events about the environment that are interesting to study. The importance of this research is to find out the environmental crimes that exist in the three novels. This type of research is a qualitative research. The data collection technique in this research is in the form of library technique. From the research results, three environmental problems are found in the three novels by Okky Madasari, namely poaching, hunting for rare animals and exploitation of the ocean. In the novel, the author not only shows various environmental crime phenomena, but is accompanied by the resolution of every environmental problem, whether it is carried out by the main character or not. Through these novels, it also appears that literary works also have a role in environmental conservation efforts.